PENGARUH GAYA KEPEMIMPINAN, TINDAKAN SUPERVISI DAN INSENTIF TERHADAP KINERJA AUDITOR INTERNAL PADA PERBANKAN DI KOTA AMBON - Tirza Oktovianti Lenggono (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2020)
This study aims to understand leadership style, supervisory actions and incentives for performance. This study uses the banking internal auditor object. This research uses multiple regression models. The response of this research is the internal auditor in Ambon city. The number of questionnaires distributed as many as 42, but only 39 returned were then sent as a sample of this study. The results showed that of the 3 hypotheses submitted, only 2 were accepted and 1 hypothesis was rejected. Hypothesis 1 shows a significant leadership style on the performance of internal auditors. Hypothesis 2 shows that supervision measures are not significant on internal auditor performance. Hypothesis 3 shows significant significance on the performance of internal auditors.